Penetration testing Azure for ethical hackers : develop practical skills to perform pentesting and risk assessment of Microsoft Azure environments /: develop practical skills to perform pentesting and risk assessment of Microsoft Azure environments. (2021) - Okeyode, David; Fosaaen, Karl
No abstract available